ANALISIS UNTUK PENERAPAN KEBIJAKAN: ANALISIS STAKEHOLDER DALAM KEBIJAKAN PROGRAM KESEHATAN IBU DAN ANAK DI KABUPATEN KEPAHIANG - Iswarno Iswarno; Mubasysyir Hasanbasri; Lutfan Lazuardi (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Maternal, neonatal and child health (MNCH)program is a national priority programs in health development.In 2006 the Ministry of Health to provides the largest budgetallocation to the KIA programs. This policy was taken in orderto accelerate the decline in maternal mortality and infant throughthe implementation of the making pregnancy safer strategy(MPS) with focus on some activities that are considered to becost effective. MNCH sustainability of the program dependson political commitment and support from stakeholders in theregion. Therefore, stakeholder analysis is important for theimplementation of policy to support the MNCH program.Objectives:Assessing the political commitment of the localgovernment to MNCH program in Kepahiang Regency.Methods: This research is a descriptive, qualitative designwith a case study. Unit of analysis is a research MNCH programstakeholder. How do the data with the brainstorming, depthinterviews, reports and documents, and direct observation.Results: Political commitment of the local government tomaternal, neonatal and child health program is still low, this isevidenced by the lack of budget allocation maternal, neonataland child health program. Essentially all stakeholders agreeand support the program. The involvement of local stakeholdersin the process of planning and budgeting programs is still lacking.Coordination among health agencies with key stakeholders inthe planning and budgeting also are not running well, so oftenthere are differencesin understanding the program. Besidesthe quality planning activities are still considered low, and thereis still weak advocacy capacity of health district office.Conclusion: The small budget allocation for the programshows the commitment to maternal, neonatal and child healthprogram of the local government is still low. This problem wasmore due to the quality of the program planning (design) that isnot well-developed. Also the role and involvement ofstakeholders in the planning process is still lacking.Keywords: Stakeholder, MNCH policy